2018
DOI: 10.3892/ijo.2018.4331
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of ASPP2 promotes the proliferation, migration and invasion of triple-negative breast cancer cells via the PI3K/AKT pathway

Abstract: Apoptosis-stimulating p53 protein 2 (ASPP2) is an apoptosis inducer that acts via binding with p53 and then enhancing the transcriptional activities toward pro‑apoptosis genes. ASPP2 has recently been reported to serve a major role in p53‑independent pathways. Triple‑negative breast cancer (TNBC) is a type of breast cancer that is more aggressive and highly lethal when p53 is mutated. In the present study, the mRNA level of ASPP2 was found to be suppressed in breast tumors compared with that in adjacent normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…We observed that both mRNA and protein levels of ASPP2 were significantly reduced after miR-30b-5p overexpression (Figures 7(a) and 7(c)), and conversely, the mRNA and protein levels of ASPP2 were increased by transfection of miR-30b-5p inhibitor in both MDA-MB-231 and HCC 1937 cells (Figures 7(b) and 7(d)). Our prophase research found that as ASPP2 siRNA inhibited the expression of ASPP2, the expression of p-AKT increased [19]. In present study, we also found that miR-30b-5p transfection significantly promoted the expression of p-AKT, whereas miR-30b-5p inhibitor resulted in the reduction of p-AKT expression (Figures 7(c) to the ASPP2, inhibit its expression and lead to the p-AKT activation.…”
Section: Aspp2 Is a Direct Target Gene Of Mir-30b-5psupporting
confidence: 73%
“…We observed that both mRNA and protein levels of ASPP2 were significantly reduced after miR-30b-5p overexpression (Figures 7(a) and 7(c)), and conversely, the mRNA and protein levels of ASPP2 were increased by transfection of miR-30b-5p inhibitor in both MDA-MB-231 and HCC 1937 cells (Figures 7(b) and 7(d)). Our prophase research found that as ASPP2 siRNA inhibited the expression of ASPP2, the expression of p-AKT increased [19]. In present study, we also found that miR-30b-5p transfection significantly promoted the expression of p-AKT, whereas miR-30b-5p inhibitor resulted in the reduction of p-AKT expression (Figures 7(c) to the ASPP2, inhibit its expression and lead to the p-AKT activation.…”
Section: Aspp2 Is a Direct Target Gene Of Mir-30b-5psupporting
confidence: 73%
“…The PI3K-AKT signaling pathway plays a central role in modulating cell proliferation, survival, and motility. 21,[24][25][26][27] In addition to promoting cell proliferation and survival, the PI3K-AKT pathway can also influence apoptotic cell death machinery. [24][25][26] DAB2IP promotes apoptosis by activating the ASK1, an upstream inducer of JNK and P38 MARK proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the human male germ cell line TCam-2 originates from seminoma, which is a type of TGCT [19]. In this context, it is worth noting that almost all NANOS1-repressed pro-apoptotic factors identified in this study (GADD45A, GADD45B, GADD45G, RHOB, and TP53BP2) are well-established tumor suppressors [27][28][29][30][31][32][33][34][35]. This is in line with NANOS1 itself being proposed to promote carcinogenesis [36].…”
Section: Discussionmentioning
confidence: 99%